2003
DOI: 10.1089/109662103322654910
|View full text |Cite
|
Sign up to set email alerts
|

The FOOTPRINTSSMModel of Pediatric Palliative Care

Abstract: Little is known about the optimal context in which to provide care for the more than 53,000 children who die each year in the United States. Poor training in pediatric palliative care contributes to care that is often fragmented and may neglect the physical, psychosocial, and spiritual needs of the child and family. Pediatric hospice care is frequently not available or not chosen by the family or health care providers. In response to a critical need to move beyond the disease oriented, hospital-based model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 6 publications
0
61
0
1
Order By: Relevance
“…27 Several studies looking specifically at advance care planning in pediatrics have reported the process to be helpful and beneficial to the family and child. [20][21][22][28][29][30][31][32] At the conclusion of our survey, most participants were offered a basic information sheet about the hospital' s Comfort and Palliative Care Team (CPCT) and a business card to contact the team. No respondents contacted the CPCT, which suggests that the parents or caregivers took the information without intention of following up with the CPCT, intended to follow-up but ultimately decided not to, or faced subsequent barriers arranging follow-up despite their intention to do so.…”
Section: (68)mentioning
confidence: 99%
“…27 Several studies looking specifically at advance care planning in pediatrics have reported the process to be helpful and beneficial to the family and child. [20][21][22][28][29][30][31][32] At the conclusion of our survey, most participants were offered a basic information sheet about the hospital' s Comfort and Palliative Care Team (CPCT) and a business card to contact the team. No respondents contacted the CPCT, which suggests that the parents or caregivers took the information without intention of following up with the CPCT, intended to follow-up but ultimately decided not to, or faced subsequent barriers arranging follow-up despite their intention to do so.…”
Section: (68)mentioning
confidence: 99%
“…The discomfort related to the term "palliative" and insufficient communication skills are well known difficulties or even barriers to the provision of PPC [4,5,24,30]. To overcome these, education in basic palliative care and communication skills in addition to PPC specialist support on site have been highlighted in previous studies [13,28]. Another reason for discomfort in communication about dying and death could also be related to moral distress on the part of the HCPs themselves [2,32]; however, to confirm the latter, a more detailed study approach would be needed.…”
Section: The Role Of Ppc Teams and A Center Of Competence Of Ppcmentioning
confidence: 99%
“…coordination of care and symptom control), and to some degree the direct support and care of a child. This kind of support has been named 'consultation service' and has been described as a reasonable and cost-effective model of care by several groups [19,28,33,34]. With respect to pediatric subspecialties, the collaboration of specialized PPC teams and pediatric oncology, cardiology, neurology, metabolic diseases and PICUs in tertiary centers and the ongoing involvement of the specialist, e.g.…”
Section: The Role Of Ppc Teams and A Center Of Competence Of Ppcmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] When unclear about the true interpretation of these data, we seek studies in literature that address these methods of analyzing plantar support in a scientific manner. [2][3][4][6][7][8][9][10][11][12][13][14][15] Some authors affirm that the plantar impression does not demonstrate the true condition of the medial longitudinal arch. However, the vast majority uses it as a method of direct evaluation of this parameter in epidemiological studies, in the assessment of normal feet, determination of normality criteria and even in flat foot classifications.…”
Section: Introductionmentioning
confidence: 99%